2003
DOI: 10.1123/jsm.17.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Involvement and Travel for Recreational Runners in North Carolina

Abstract: This study utilized an adaptation of the uni-dimensional involvement scale developed by Josiam, Smeaton, and Clements (1999) to test Havitz and Dimanche's Proposition XI, which states that “an individual's involvement profile with a recreational activity, tourist destination, or related equipment is positively related to frequency of participation, travel, or purchase” (1990, p. 189). Relationships between recreational runners' involvement in travel to road races and behavioral characteristics, including prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 26 publications
6
69
0
3
Order By: Relevance
“…In addition, the regression analysis revealed that not only did past experience in their sport (as measured by the number of years registered or number of swimming competitions competed in the past year) not play a significant role in whether the participants traveled to compete in the championships, but it also did not display any significance in whether they would compete (Table 4). It may be that the sample could be classified as highly involved in their sport consistent with results reported by McGehee, Yoon, and Cardenas (2003). Those who felt more motivated to compete in their sport of choice, in this case the 2006 short course swimming championships, were less likely to be motivated to travel for its own sake.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, the regression analysis revealed that not only did past experience in their sport (as measured by the number of years registered or number of swimming competitions competed in the past year) not play a significant role in whether the participants traveled to compete in the championships, but it also did not display any significance in whether they would compete (Table 4). It may be that the sample could be classified as highly involved in their sport consistent with results reported by McGehee, Yoon, and Cardenas (2003). Those who felt more motivated to compete in their sport of choice, in this case the 2006 short course swimming championships, were less likely to be motivated to travel for its own sake.…”
Section: Discussionsupporting
confidence: 62%
“…McGehee, Yoon, and Cardenas (2003) found that running competitors participated in more than one race a year that required overnight travel. Interestingly, they found a difference in the participation level of those traveling to participate in a sport and their past experience with the sport.…”
Section: Sport and Travel Motivationsmentioning
confidence: 99%
“…The current study utilized a consumer acculturation framework to investigate specific aspects of the culture experience. In addition, tourism research has not examined prior sport experiences such as involvement and a desire to participate in organized events, which are likely to serve as equally important motives for international travel (Carroll & Alexandris, 1997;McGehee, Yoon, & Cardenas, 2003). Therefore, the current study examined involvement with running and strength of motivation towards running events as motives for international travel.…”
Section: Introductionmentioning
confidence: 93%
“…The term of active sports tourists [11] refers to people who travel to the place where a sporting event is organized and actively participate in that event [12] [13]. Recreational runners have been considered in this category [12] [14] as non-elite sporting competitions [7] attract a lot of participants, which have often been used in destination marketing.…”
mentioning
confidence: 99%